Bridging the digital divide in the G20: Skills for the new age - Krish Chetty; Urvashi Aneja; Vidisha Mishra; Nozibele Gcora; Jaya Josie (Kiel Institute for the World Economy (IfW), 2017)
The digital divide in general, and between women and men in particular, is a manifestation of exclusion, poverty and inequality, and is likely to continue because of the effects of unemployment, poorly functioning digital skilling programmes and socio-cultural norms in some economies, and further depriving women equal access to digital services. Digital skills provide the poor a catalyst to break out of the cycle of poverty and empower themselves. This paper considers a three-pronged digital skills strategy that will be required for developing countries to break out of the digital divide trap: (1) Monitor the evolving set of digital skills required for employment (2) incorporate a holistic digital skills development strategy into national education programmes, and (3) contextualize skilling programs within prevailing socio-cultural norms that will shape the uptake and impact of digital skilling programs.
Keywords: C83; J20; J22; J23; J24; F63; F66; F68; I24; I25; O15; O19; 330; Digital skills; digital divide; digitalization; information literacy; computer literacy; media literacy; communication literacy; technology literacy; socio-cultural norms